Curcumin Ameliorates Cisplatin-Induced Nephrotoxicity and Potentiates Its Anticancer Activity in SD Rats: Potential Role of Curcumin in Breast Cancer Chemotherapy - Kumar, Parveen; Barua, Chandana C.; Sulakhiya, Kunjbihari; Sharma, Rajeev Kumar (Frontiers in Pharmacology, 2017)
Breast malignant neoplastic disease is one of the most complex diseases, as it is a multifactorial disease in which virtually all the targets are instantly or indirectly inter-reliant on each other. Cisplatin (CIS), an inorganic antineoplastic agent is widely utilised in the treatment of various solid tumours including breast cancer. Despite everything, its clinical use is limited, due to ototoxicity, peripheral neuropathy and nephrotoxicity. The present work was directed to assess the combined result of curcumin (CUR) and CIS in 7, 12-dimethyl benz[a]anthracene (DMBA) induced breast cancer in rats and the prevention of nephrotoxicity induced by the latter. CIS-induced nephrotoxicity was assessed by change in body weight, kidney weight, altered levels of BUN, creatinine, TNF-α, IL-6, IL-8, IL-10 and histopathology of the kidney. Anticancer activity was assessed by measurement of tumour weight, tumour volume, % tumour inhibition, levels of PPAR-γ and BDNF in mammary tumours and histopathology of mammary tumours. CUR pre-treatment mitigated nephrotoxicity by reducing the inflammatory markers (TNF-α, IL-6 and IL-8; p<0.001). Further, it reduced mammary cancer via increasing the expression of PPAR-γ (p<0.001) and decreasing the expression of BDNF (p<0.001) in mammary tumours. It also reduced tumour volume, further postulating that CUR might adjunct the anticancer activity of the CIS. To the best of our knowledge, this is the first report, which showed that CUR ameliorated CIS-induced nephrotoxicity and improved its anticancer activity in DMBA induced breast cancer in female Sprague-Dawley rats.